Consulting Report – Bigmond S.A.C. Outplacement Service Business Plan - Pacheco Razuri, David Alonso (2020)
The opportunity of no massified digital outplacement service for individuals currently offered in the market is receiving considerable additional attention due to the COVID-19 pandemic. This paper emphasizes on identifying and analyzing if the opportunity is relevant for the Peruvian market and, furthermore, establishes a concept for Bigmond to investigate if this opportunity is exploitable. Literature has shown that the labor market is experiencing a complete change because of digitalization. By conducting qualitative and quantitative analysis on existing practices in the outplacement industry worldwide, plus, by evaluating the potential of the target country and Bigmond through the PESTEL and AMOFHIT framework, dark areas of information on how to offer outplacement services properly have been illuminated. Research emphasizes the importance of the satisfaction of end-clients through personal decision-making, individualization and communication in the outplacement service. Additionally, outplacement agencies act as supportive bridge between employer and employee, especially in emergency situations, such as COVID-19. Hence, it is advisable to provide a differentiated service that, rather than offering the outplacement service itself, will allow individuals to connect with companies, mentors, and coaches during their journey of unemployment.